DIGITAL EDUCATION : ONLINE REGISTRATION AS AN EFFORT TO IMPROVE ADMINISTRATIVE EFFICIENCY - Gustina Irawan, Yeyen; Oktaria, Rina; Pordaningsih, Reny (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Digital transformation in the healthcare sector encourages health service facilities to improve administrative efficiency through the use of technology, including online registration systems. Dr. Bratanata Hospital Jambi has provided an online registration service; however, initial survey results indicate that its utilization rate remains low due to limited patient understanding and insufficient socialization. This community service program aims to improve the digital literacy of patients and their families through education, training, and assistance in using the online registration system as an effort to support administrative efficiency in the hospital. The methods implemented include direct socialization in the outpatient area, demonstrations of the application/website registration process, distribution of digital educational materials, and one-on-one assistance for patients using the online registration system for the first time. Evaluation was conducted using pre-test and post-test assessments to measure knowledge improvement, as well as observation of the number of patients using the online registration system after the activity. The results show a significant increase in patients' understanding of the online registration steps, a rise in the proportion of online registration users, and a reduction in queue length at the administrative counters during peak hours. This program demonstrates that digital education can enhance the utilization of health service technologies and support administrative efficiency in hospitals. It is recommended that this activity be continued regularly to ensure sustainability and equitable digital literacy among patients.